Carlos Alberto Seguin, at 75 years of his clinical work at the Hospital Nacional Guillermo Almenara Irigoyen - Huarcaya Victoria, Jeff (2016)
In February 2016, we commemorate the 75th foundation anniversary of the Hospital Nacional Guillermo Almenara Irigoyen (HNGAI), formerly known as Hospital Obrero de Lima. Among the prominent doctors who worked in this hospital, we want to highlight the figure of Carlos Alberto Seguin, master of Peruvian Psychiatry. He joined the hospital as a neuro-psychiatrist since its foundation in 1941, and in 1942 he joined the Department of Psychiatry at the Medical School of San Fernando. He participated in academic activities during the second half of the twentieth century, when changes occurred in the Peruvian psychiatry, like phenomenology and neuroscience integration with psychosocial and psychodynamic orientation. Seguin reintroduced psychodynamic and psychosomatic ideas with vigor and passion, thus enriching the Peruvian Psychiatry founded by Valdizán and led by Delgado. Seguin’s lessons transcended Psychiatry itself to the basic training of the general physician. His work can be summarized as a form of reaction against the dehumanizing scientism which turned man into a machine repairable by a technician. The master's teachings marked the HNGAI identity.